2017
DOI: 10.1186/s13104-017-2617-6
|View full text |Cite
|
Sign up to set email alerts
|

Generic atorvastatin is as effective as the brand-name drug (LIPITOR®) in lowering cholesterol levels: a cross-sectional retrospective cohort study

Abstract: BackgroundIn a world of ever increasing health care costs, generic drugs represent a major opportunity to ensure access to essential medicines for people who otherwise would be unable to afford them. However, some clinicians and patients are still questioning the safety and effectiveness of generic formulations compared to the proprietary drugs necessitating further systematic research analyzing the generic drugs’ efficacy. Our objective was to compare the lipid lowering effects of generic and branded atorvast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 10 publications
(11 reference statements)
0
15
0
Order By: Relevance
“…Mano et al [ 41 ], in a retrospective study, reported that changing from brand-name ( N = 147) to generic atorvastatin ( N = 135) did not affect treatment persistence (85.9% vs. 73.5%) in patients, after 180 days of treatment. On the basis of 266 patients, Loch et al [ 42 ] concluded that brand-name vs. generic atorvastatin achieved similar results (total and LDL cholesterol) in the clinical management of dyslipidemia, except for HDL-c levels (better with brand-name atorvastatin). Nevertheless, to our understanding, the following should be assessed: whether the sample size obtained was adequate (statistical power), where the balance would be between statistical significance and clinical relevance/impact, and when meta-analyses are performed based on these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Mano et al [ 41 ], in a retrospective study, reported that changing from brand-name ( N = 147) to generic atorvastatin ( N = 135) did not affect treatment persistence (85.9% vs. 73.5%) in patients, after 180 days of treatment. On the basis of 266 patients, Loch et al [ 42 ] concluded that brand-name vs. generic atorvastatin achieved similar results (total and LDL cholesterol) in the clinical management of dyslipidemia, except for HDL-c levels (better with brand-name atorvastatin). Nevertheless, to our understanding, the following should be assessed: whether the sample size obtained was adequate (statistical power), where the balance would be between statistical significance and clinical relevance/impact, and when meta-analyses are performed based on these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not investigate the dose-response relationship between ATO and hepatotoxicity in the study because only patients who had both the marker and index drugs were included in the analyses. Third, although generic ATO is as effective as the brand-name drug in lowering cholesterol levels,49 we didn’t distinguish whether ATO was a generic or brand name drug because of the limited sample size.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Mano [48], in a retrospective study, reported that switching between brand-name (N = 147) and generic (N = 135) atorvastatin did not affect patients' treatment persistence (85.9% vs. 73.5%) after 180 days of treatment. Loch enrolled 266 patients in his study [49]. He concluded that brand-name vs. generic atorvastatin achieved similar results in terms of total cholesterol and low-density lipoprotein cholesterol in the clinical management of dyslipidemia, although brand-name atorvastatin achieved improvements in high-density lipoprotein cholesterol.…”
Section: Discussionmentioning
confidence: 99%